PROSES MORFOLOGIS BAHASA GAUL PADA MEDIA SOSIAL INSTAGRAM - Ratriyana, Putu Tarisha Angira; Jenisya, Nisa (Prosiding Seminar Nasional Bahasa Ibu, 2025)
This study aims to analyze the morphological processes in Indonesian slang language used on Instagram, focusing on comments in @windahbasudara’s account. Unlike previous studies that examined slang within specific communities or on other platforms such as Facebook, this research highlights the use of Indonesian slang used by Gen Z on Instagram. Using a qualitative descriptive method and Kridalaksana’s morphological theory, the study identifies distinctive morphological patterns, including new variations in affixation, reduplication, and abbreviation. One of the key findings is the use of confixes with a more flexible pattern, as well as innovations in word shortening. This phenomenon reflects the linguistic creativity of users especially Gen Z in adapting to technological advancements and popular culture. The study concludes that slang enriches the Indonesian vocabulary.